#### Answer

$\frac{3}{11}$

#### Work Step by Step

$\frac{1}{3}$*$\frac{9}{11}$=
$\frac{1*9}{3*11}$=$\frac{9}{33}$=$\frac{3}{11}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{3}{11}$

$\frac{1}{3}$*$\frac{9}{11}$=
$\frac{1*9}{3*11}$=$\frac{9}{33}$=$\frac{3}{11}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.